Use of a Knowledge-Based Governance Approach to Plan a Post-COVID-19 Predoctoral Dental Curriculum - Natasha M. Flake; Daniel C. N. Chan; Arthur C. DiMarco; Bruce D. Silverstein (MDPI AG, 2021)
COVID-19 abruptly changed dental education, forcing educators out of their comfort zones and into using new technologies and teaching approaches. At the University of Washington School of Dentistry, a task force evaluated the curricular changes that resulted from COVID and made recommendations for the future predoctoral dental curriculum. This manuscript reports the process employed, the findings of the task force, and how these findings will impact the curriculum. A knowledge-based governance (KBG) approach was employed. KBG focuses on gathering all relevant information and identifying all choices. It separates dialogue from deliberation. Information was gathered via literature review, focus group interviews, electronic surveys, and other metrics. The task force evaluated: (1) delivering didactic content remotely; (2) administering assessments remotely; (3) duplicating preclinical simulation lab courses due to social distancing; and (4) the conversion from a numerical to a credit/no credit grading scale. Key recommendations resulted from focus groups and electronic surveys that allowed any student or faculty member an opportunity to provide input. Some topics were relatively non-controversial and strong recommendations were evident. The most controversial issue was which grading scale should be utilized. A KBG approach is an effective means to address mega issues in the dental school environment.